2016
DOI: 10.1186/s12913-016-1627-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nurse-delivered community-based CD4 services on facilitating pre-ART care in rural South Africa

Abstract: BackgroundHIV testing, diagnosis and treatment programs have expanded globally, particularly in resource-limited settings. Diagnosis must be followed by determination of treatment eligibility and referral to care prior to initiation of antiretroviral treatment (ART). However, barriers and delays along these early steps in the treatment cascade may impede successful ART initiation. New strategies are needed to facilitate the treatment cascade. We evaluated the role of on site CD4+ T cell count phlebotomy servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…This intervention has the potential to substantially reduce TB and HIV incidence simultaneously by expanding ART, IPT, and both first- and second-line TB treatment coverage. A number of recent studies have shown that home or community-based HIV testing and counseling is very effective and cost-effective in rural South Africa, with the potential to substantially reduce HIV incidence and associated mortality [6, 6064]. These studies have established that a decentralized approach to HIV testing is not only both feasible and well accepted by patients, but that linkage to care and ART initiation occurs with subsequent virologic suppression.…”
Section: Discussionmentioning
confidence: 99%
“…This intervention has the potential to substantially reduce TB and HIV incidence simultaneously by expanding ART, IPT, and both first- and second-line TB treatment coverage. A number of recent studies have shown that home or community-based HIV testing and counseling is very effective and cost-effective in rural South Africa, with the potential to substantially reduce HIV incidence and associated mortality [6, 6064]. These studies have established that a decentralized approach to HIV testing is not only both feasible and well accepted by patients, but that linkage to care and ART initiation occurs with subsequent virologic suppression.…”
Section: Discussionmentioning
confidence: 99%
“…For those who voluntarily sought services, staff members administered a brief survey that included demographic characteristics, previous HIV testing, previous TB treatment, and current TB symptoms (cough, fever, night sweats, weight loss, chest pain, hemoptysis). We deployed a 2-step (screen and confirmation) rapid HIV testing strategy, and phlebotomy was offered for CD4 testing if positive [ 23 , 24 ]. Individuals with cough >2 weeks or > 2 other symptoms were requested to produce 2 sputum specimens to be tested using AFB smear and culture with DST [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to literature [16], the implementation of an art specialty strategy for rural revitalization benefits from the political advantages of the party's leadership, the benefits of the socialist system, the creative spirit of farmers, strong economic strength, long agricultural civilization, strong market demand, and other conditions and capabilities. With the continuous enrichment of material life and the increasing diversification of people's needs, it is difficult to meet the daily needs of the people solely by relying on the government's art professional service.…”
Section: Related Workmentioning
confidence: 99%